The Preservation of Ren Zhuang Nuo Drama in Shan Xi, China - Ying, Zhang; Roongruang , Panya; Yuxin, Zhang; Lertsivaporn , Jirapat; Aroonwong, Nitaya (Journal of Roi Kaensarn Academi, 2024)
Purposes of the research were: (1) To Study the traditional performing art of Ren Zhuang Nuo Drama in Shanxi, China. (2) To write the hand book of Han musical identity of Ren Zhuang Nuo Drama. (3)To use the hand book of Ren Zhuang Nuo Drama for preservation, I will give a lecture for 200 people to spread the Ren Zhuang Nuo Drama. Research methodology is qualitative research. From the perspective of data analysis, this research plan chooses qualitative research, and the results of the research depend on the nature, characteristics and natural development of the thing itself. From the perspective of knowledge type, this research is social research, which requires researchers to go deep into the local area the community went to conduct field interviews and field surveys. In terms of methodology, this research needs to conduct side-by-side literature mining on local history, ethnography, and ancient books.